Eat, play, live: a randomized controlled trial within a natural experiment examining the role of nutrition policy and capacity building in improving food environments in recreation and sport facilities - Dana Lee Olstad; Kim D. Raine; Rachel J. L. Prowse; Dona Tomlin; Sara F. Kirk; Jessie-Lee D. McIsaac; Louise C. Mâsse; M. Susan Caswell; Rhona M. Hanning; Todd Milford; Patti-Jean Naylor (BMC, 2019)
Abstract Background Recreation and sport facilities often have unhealthy food environments that may promote unhealthy dietary patterns among children. In response, some Canadian provinces have released voluntary nutrition guidelines for recreation and sport facilities, however implementation has been limited. Organizational capacity building may overcome barriers to implementing guidelines. Eat, Play, Live was a randomized controlled trial embedded within a natural experiment that tested the impact of an 18 month capacity building intervention (CBI) in enhancing implementation of provincial nutrition guidelines, and whether nutrition guidelines were associated with positive changes. Primary outcomes were facility capacity, policy development and food environment quality. Methods Recreation and sport facilities in three guideline provinces were randomized into a guideline + CBI (GL + CBI; n = 17) or a guideline only comparison condition (GL-ONLY; n = 15). Facilities in a province without guidelines constituted a second comparison condition (NO-GL; n = 17). Facility capacity, policy development, and food environment quality (vending and concession) were measured and compared at baseline and follow-up across conditions using repeated measures ANOVA and Chi-square statistics. Healthfulness of vending and concession items was rated as Do Not Sell (least nutritious), Sell Sometimes or Sell Most (most nutritious). Results There were significant time by condition effects, with significant increases in facility capacity (mean ± SD: 30.8 ± 15.6% to 62.3 ± 22.0%; p <  0.01), nutrition policy development (17.6% developed new policies; p = 0.049), overall quality of the concession food environment (14.7 ± 8.4 to 17.5 ± 7.2; p <  0.001), and in the proportion of Sell Most (3.7 ± 4.4% to 11.0 ± 9.0%; p = 0.002) and Sell Sometimes vending snacks (22.4 ± 14.4% to 43.8 ± 15.8%; p <  0.001) in GL + CBI facilities, with a significant decline in Do Not Sell vending snacks (74.0 ± 16.6% to 45.2 ± 20.1%; p <  0.001). Conclusions Significant improvements in facility capacity, policy development and food environment quality occurred in recreation and sport facilities that were exposed to nutrition guidelines and participated in a CBI. Outcomes did not improve in facilities that were only passively or not at all exposed to guidelines. Ongoing capacity building may enhance implementation of voluntary nutrition guidelines, however food environments remained overwhelmingly unhealthy, suggesting additional scope to enhance implementation. Trials registration Clinical trials registration (retrospectively registered): ISRCTN14669997 Jul 3, 2018.